(untitled) (Universal International Scientific Journal, 2026)
This article covers the issue of disorganized youth and their social adaptation in a comprehensive manner. In particular, it covers the relationship between social and psychological adaptation and the individual’s life strategy. In particular, it analyzes the factors that affect the low level of self-activation and self-improvement of disorganized youth with a high level of social maladjustment.